2016
DOI: 10.1016/j.semcancer.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperthermia as a mitigation strategy in DNA damage-based cancer therapies

Abstract: Utilization of thermal therapy (hyperthermia) is defined as the application of exogenous heat induction and represents a concept that is far from new as it goes back to ancient times when heat was used for treating various diseases, including malignancies. Such therapeutic strategy has gained even more popularity (over the last few decades) since various studies have shed light into understanding hyperthermia's underlying molecular mechanism(s) of action. In general, hyperthermia is applied as complementary (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 112 publications
(112 reference statements)
1
42
0
Order By: Relevance
“…Conversely, promotion of carcinogenesis and progression of tumors are both caused by defective apoptosis [6]. Apoptosis is an important mechanism of hyperthermia-induced cell death [7]. ROS generation is an upstream regulator of the mitochondria-mediated apoptosis pathway, which controls cell proliferation and cell death, cell migration, mitochondrial calcium loading, and other cellular functions [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, promotion of carcinogenesis and progression of tumors are both caused by defective apoptosis [6]. Apoptosis is an important mechanism of hyperthermia-induced cell death [7]. ROS generation is an upstream regulator of the mitochondria-mediated apoptosis pathway, which controls cell proliferation and cell death, cell migration, mitochondrial calcium loading, and other cellular functions [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…Local hyperthermia has been successfully applied to treat cancer, and deep fungal, bacterial and viral skin infections. [3][4][5] To our knowledge, this is the first report to describe the clinical efficacy of hyperthermia in a patient with multiple SGA, and we presumed that hyperthermia possibly treated SGA by modulating the cellular immune response. In the context that the patient failed to respond to alternative therapies, local hyperthermia might be safe and effective as a second-line treatment option for patients who have exhausted more conventional therapies.…”
mentioning
confidence: 81%
“…Accumulating studies have reported that hyperthermia exerts multiple effects including direct killing of tumor cells via protein denaturation, DNA aggregation and cross‐linking, activating apoptotic pathways, changes in cell cycle regulatory signaling pathways, alterations in the tumor microenvironment, activation of heat shock proteins, induction of the immune response, alterations in blood flow, and oxygen and nutrient distribution at the tumor site . When BT‐474 cells are treated with magnetic nanoparticles and mitomycin‐C in the presence or absence of hyperthermia, it is reported that hyperthermia intensifies inhibitory effects of nanoparticles and mitomycin‐C on the expression levels of MDR‐associated proteins . Inactivation of drug detoxification mechanisms, increase in the drug uptake, induction of apoptosis, enhancement of drug cytotoxicity, and reduction in cell membrane localization of MDR proteins are other effects mediated by hyperthermia, which circumvent MDR in various cancers …”
Section: Novel Strategies Against Mdrmentioning
confidence: 99%
“…81,82 When BT-474 cells are treated with magnetic nanoparticles and mitomycin-C in the presence or absence of hyperthermia, it is reported that hyperthermia intensifies inhibitory effects of nanoparticles and mitomycin-C on the expression levels of MDR-associated proteins. 83 Inactivation of drug detoxification mechanisms, increase in the drug uptake, induction of apoptosis, enhancement of drug cytotoxicity, and reduction in cell membrane localization of MDR proteins are other effects mediated by hyperthermia, which circumvent MDR in various cancers. 84 The application of ultrasound therapy to enhance therapeutic efficacy against cancer cells has been the subject of various clinical investigations.…”
Section: Physical Approaches To Overcome Mdrmentioning
confidence: 99%